Analisis Emisi Konduksi Perangkat Kompor Induksi di Frekuensi 150 kHz-30 MHz - Budi Sudiarto; Henny Tri Kurniawati (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
Induction cooker usage is predicted to replace conventional cookers due to efficiency and energy resilience advantages. These energy conservation efforts are also the government efforts in reducing the energy crisis related to the liquified petroleum gas (LPG) supply. However, household appliances, including induction cooker using inverter technology, have the potential to cause electromagnetic interference (EMI) in the form of conducted emissions, which can be interpreted as noise currents propagating along conduction paths and potentially disrupting other electronic equipments through the voltage source. Regulations related to electromagnetic interference from induction cookers are listed in the Comité International Spécial des Perturbations Radioélectriques (CISPR) 14-1:2020. This research aimed to identify the induction cooker distribution with regard to electromagnetic interference requirements, namely conducted emissions, according to CISPR 14-1:2020. The conduction emission measurement was conducted on four induction cooker brands circulating in the community (A, C, M, and P) in various cooking modes and power levels in the frequency range of 150 kHz–30 MHz, with PLN electric voltage of 220 V and frequency of 50 Hz. Measurements were performed ten times for each stage, and the six highest conduction emission values were obtained. Based on measurements in the frequency range of 150 kHz–30 MHz, it was found that the conducted emission levels in most induction cookers exceeded the CISPR 14-1:2020 standard. In the future, induction cooker components must pay more attention to regulations regarding conducted emissions to ensure that these household appliances are increasingly safe and environmentally comfortable in the electromagnetic environment.